Non-monochromatic laser assist scattering in thermal environment - Saddam Husain Dhobi; Kishori Yadav; Suresh Prasad Gupta; Jeevan Joyti Nakarmi; Ajay Kumar Jha (Journal of Nigerian Society of Physical Sciences)
This study aims to investigate the differential cross-section (DCS) in a non-monochromatic laser-assisted thermal environment. Building on existing research, which primarily explores electron dynamics and ionization processes without considering thermal effects, this work seeks to bridge this research gap by examining the DCS under non-monochromatic laser fields in a thermal environment. The methodology involves utilizing a vector potential derived by Milosvic to represent non-monochromatic laser fields and applying a semi-classical approximation with the help of Volkov solutions. The S-matrix is then obtained to study the DCS. The developed model was computed to analyze the nature of the DCS. The results indicate that the DCS for photon absorption is higher than for emission due to atomic oscillation/excitation. This causes atom expansion upon absorption and a decrease in field strength during emission. Furthermore, the DCS behavior varies with the phase of the non-monochromatic wave and polarization, with distinct patterns observed for absorption and emission scenarios. The DCS with energy at different rates of absorption and emission exhibits a damping nature. Additionally, the DCS shows oscillatory behavior with separation distance, displaying higher values for absorption and varying with laser phase. The findings provide valuable insights into electron-atom interactions under laser fields in thermal conditions, with implications for quantum thermal machines, photochemistry, proton exchange membrane fuel cells (PEMFC), and more.